Tingkat Pengetahuan Dan Perilaku Swamedikasi Penggunaan Obat Bebas Pada Masyarakat Di Kecamatan Simpang Kanan Kabupaten Rokan Hilir - Ayu Rahmawati; Nursyafni; Novtafia Endri; Muhammad Arif; Nawwar Irfan; Wulandari, Tri Ayu; Fitratul Wahyuni (The Journal Of Pharmacy, 2024)
Self-medication is an act of self-medication carried out by the community to maintain health or manage disease based on personal diagnosis, using drugs repeatedly. This study aims to analyze the relationship between knowledge level and self-medication behavior using over-the-counter drugs in the community in Simpang Kanan District, Rokan Hilir Regency. The research was conducted observational with a cross-sectional approach, using quota sampling technique and questionnaires as instruments. The results showed that out of 90 respondents, 77.8% had good knowledge, 21.1% had sufficient knowledge, and 1.1% had poor knowledge. In terms of behavior, 81.1% had good behavior, while 18.9% had moderate behavior in self-medication. Analysis using the Chi-Square test resulted in a p-value of 0.002 (p<0.05), indicating a significant relationship between the level of knowledge and behavior of self-medication using over-the-counter drugs in the community in Simpang Kanan District, Rokan Hilir Regency.